Job creation in Latin America in the 1990s : the foundation for social policy - Stallings, Barbara (ECLAC SantiagoCL, 2001)
Analyzes labour market trends in Latin America and the Caribbean in the 1990s, arguing that employment must be the foundation of a social policy strategy for the region.